Evolution of pediatric epilepsy surgery program over 2000–2017: Improvement of care?. (May 2019) - Belohlavkova, Anezka; Jezdik, Petr; Jahodova, Alena; Kudr, Martin; Benova, Barbora; Maulisova, Alice; Liby, Petr; Vaculik, Miroslav; Lesko, Robert; Kyncl, Martin; Zamecnik, Josef; Tichy, Michal; et al.
Abstract: Purpose: We assessed trends in spectrum of candidates, diagnostic algorithm, therapeutic approach and outcome of a pediatric epilepsy surgery program between 2000 and 2017. Methods: All pediatric patients who underwent curative epilepsy surgery in Motol Epilepsy Center during selected period (n = 233) were included in the study and divided into two groups according to time of the surgery (developing program 2000–2010: n = 86, established program 2011–2017: n = 147). Differences in presurgical, surgical and outcome variables between the groups were statistically analyzed. Results: A total of 264 resections or hemispheric disconnections were performed (including 31 reoperations). In the later epoch median age of candidates decreased. Median duration of disease shortened in patients with temporal lobe epilepsy. Number of patients with non-localizing MRI findings (subtle or multiple lesions) rose, as well as those with epileptogenic zone adjacent to eloquent cortex. There was a trend towards one-step procedures guided by multimodal neuroimaging and intraoperative electrophysiology; long-term invasive EEG was performed in fewer patients. Subdural electrodes for long-term invasive monitoring were almost completely replaced by stereo-EEG. The number of focal resections and hemispherotomies rose over time. Surgeries were more often regarded complete. Histopathological findings of resected tissue documented developing spectrum of candidates. 82.0% of all children were seizure-free two years after surgery; major complications occurred in 4.6% procedures; both groups did not significantly differ in these parameters. Conclusion: In the established pediatric epilepsy surgery program, our patients underwent epilepsy surgery at younger age and suffered from more complex structural pathology. Outcomes and including complication rate remained stable. Highlights: Shift towards more complex structural pathology in surgical candidates. Median age of children undergoing surgery decreased (median difference 1.8 years). Increased use of focal resections and hemispherotomies, mostly one-step procedures. Stable outcomes (seizure, AED, cognitive) as well as complication rate.